2015
DOI: 10.1111/bjet.12244
|View full text |Cite
|
Sign up to set email alerts
|

A research analytics framework‐supported recommendation approach for supervisor selection

Abstract: Identifying a suitable supervisor for a new research student is vitally important for his or her academic career. Current information overload and information disorientation have posed significant challenges for new students. Existing research for supervisor identification focuses on quality assessment of candidates, but ignores indirect relevance with candidate supervisors' previous students, social network connections and their thinking styles. This paper presents a comprehensive student-centric approach bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…We used Average Rate (AR) [6] and Normalized Discounted Cumulative Gain (NDCG) [6] as the Table 2 reports AR values of the user ratings for both retrieval models in the three different settings. It can be easily observed that for both retrieval models, the Custom setting of criteria/subcriteria performs better, and between the TF/IDF and BM25 algorithms, in most cases, the BM25 based algorithm performs better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Average Rate (AR) [6] and Normalized Discounted Cumulative Gain (NDCG) [6] as the Table 2 reports AR values of the user ratings for both retrieval models in the three different settings. It can be easily observed that for both retrieval models, the Custom setting of criteria/subcriteria performs better, and between the TF/IDF and BM25 algorithms, in most cases, the BM25 based algorithm performs better.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [6] presented a Research Analytics Framework for Education (RAF-E), this being a student centric method for finding and recommending supervisors for new postgraduate students, considering different metrics from 3 dimensions: relevance, connectivity, and quality. Zhang et al [7] proposed a personality-matching aided approach for supervisor recommendation based on their previous work [6], which integrates objective measurements (relevance, connectivity, and quality) and subjective personality matching, to get a list of supervisors to recommend.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The model emphasizes on the fact that when a student with specific set of skills is successful in a course then another student with similar set of skills will have higher success rate in the said course. In 2016, Zhang et al have presented a comprehensive novel approach based on research analytics framework for finding and recommending supervisors for new students. The system integrates multiple measurements from three dimensions, that is, relevance, connectivity, and quality to generate more satisfactory recommendations.…”
Section: Related Workmentioning
confidence: 99%
“…Research analytics Zhang et al (2015) present a research analytics framework for matching doctoral students and supervisors. The analytics use multiple measurements on three dimensions (relevance, connectivity and quality) to do the matching.…”
Section: Data Display and Data Visualisation: Making The Data Analysesmentioning
confidence: 99%